Immune reconstitution following umbilical cord blood transplantation: IRES, a study of UK paediatric patients. Issue 1 (21st May 2020) - Girdlestone, John; Raymond, Meera; Shaw, Bronwen; Tulpule, Sameer; Devlia, Vikesh R.; Danby, Robert; Ahyee, Trudy; Saudemont, Aurore; Hough, Rachael; Veys, Paul; Ruggeri, Annalisa; Vora, Ajay; et al.
Abstract: To obtain a qualitative as well as quantitative view immune reconstitution following umbilical cord blood (UCB) transplantation of paediatric patients, we utilised a broad panel of flow cytometry markers to monitor the phenotypes of lymphoid and myeloid cells at 1‐12 months post‐transplant. Samples were received from 46 patients with a median age of 3.3 years and survival was 76% at 1 year. Monocytes were at similar or higher median levels than in adult controls at all times tested, with a high CD16+ proportion in the first 3 months. NK cells were also within adult ranges, with a CD56++ high proportion in the first 6 months. B cell recovery was seen from 2 months in most patients and T cells from 3 months, both were delayed with anti‐thymocyte globulin (ATG) treatment. CD4:CD8 ratios were high in the first 6 months, and the proportion of T cells with recent thymic emigrant and naïve phenotypes rose from 3 months. NK and plasmacytoid dendritic cell numbers remained at reduced levels in patients not surviving to 1 year. Our results can serve as a useful reference for detailed monitoring of immune reconstitution in paediatric recipients of UCB.